Pemidanaan Terhadap Pelaku Pasif Tindak Pidana Pencucian Uang (Studi Putusan Nomor 488/Pid.B/2021/PN JKT.BRT): Punishment of Passive Perpetrators Laundering Crimes (Decision Study Number 488/Pid.B/2021/PN Jkt.Brt) - Widyatori Haritz Diamor; Ermania Wijajanti (Reformasi Hukum Trisakti, 2025)
Money laundering constitutes the act of concealing proceeds derived from criminal activities, referred to as the follow-up crime. In Decision No. 488/Pid.B/2021/PN Jkt.Brt, the predicate offence (core crime) under the Article No.8 of 2010 in conjunction with Article 55(1) of the Indonesian Criminal Code (KUHP) was not proven. The issue addressed in this article is the legal basis upon which the court adjudicated the follow-up crime of money laundering in the absence of a proven core crime, as stipulated under Law No.8 of 2010 in conjunction with Article 55(1) point 1 of the KUHP. This study employs a normative legal research method, utilizing secondary data and adopting a descriptive-analytical approach. The analysis is conducted qualitatively, with conclusion drawn deductively. The findings and conclusion of this study is the court lacks a legal basis to adjudicate the money laundering as a follow-up crime without the presence of proven predicate crime or core crime, in accordance with Article 5 of Law No. 8 of 2010 in conjunction with Article 55(1) point 1 of the KUHP. Consequently, adhering to the principle of nullum crimen sine culpa (no crime without fault), the defendant cannot be held criminally liable.